
#1
Sep2010, 10:39 PM

P: 122

Why is the equation
(A) n!/(nk)! = n(n1)(n2)...(nk+1) true? For example, let n=4 and k=2, then 4!/2! = 4x3x2x1 / 2x1 = 4x3 = 12. I understand this example, but I can't make the connection with this and the righthandside of equation (A). For example, why is our example above not 4!/2! = 4(41)(42)...(42+1). I know this doesn't make any mathematical sense, but I can't understand how the equation on the righthandside of (A) is derived. Thanks for your help. M 



#2
Sep2010, 11:05 PM

Sci Advisor
HW Helper
Thanks
P: 25,175

The equation is an informal shorthand. You aren't supposed to include (n2) as a factor in the case where n=4 and k=2. You are supposed to STOP at (nk+1)=3.




#3
Sep2110, 02:48 AM

Admin
P: 22,709

Adding to what Dick wrote  it may become more obvious when you try to derive the equation.
[tex]\frac {n!} {(nk)!} = \frac {n \times (n1) \times (n2) \times ... \times (n  k + 1) \times (n  k) \times (n  k 1) \times ... \times 3 \times 2 \times 1} {(nk) \times (nk1) \times (nk2) \times ... \times 3 \times 2 \times 1} [/tex] Check what cancels out and what is left. And remember that when n and k are too small it is not possible to explicitly list all these terms. 


Register to reply 
Related Discussions  
Factorial Sum  General Math  20  
Why is zero factorial equal to 1?  General Math  18  
Factorial of 0=1 ?!!  Linear & Abstract Algebra  17  
what is the mean of factorial(1/2)??  Calculus  12  
n factorial  Calculus  7 